Online Fundraising, Self-Image, and the Long-Term Impact of Ask Avoidance - Maja Adena; Steffen Huck (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
We provide the first field evidence for the role of pure self-image, independent of social image, in charitable giving. In an online fundraising campaign for a social youth project run on an opera ticket booking platform we document how individuals engage in self-deception to preserve their self-image. In addition, we provide evidence on stark adverse long-run effects of the fundraising campaign for ticket sales. Ävoiding the ask,öpera customers who faced more insistent online fundraising buy fewer tickets in the following season. Our results suggest that fundraising management should not decide in isolation about their campaigns, even if very successful. Rather broader operational concerns have to be considered.
Keywords: D64; D03; D12; C93; L31; 330; online fundraising; quasi-experiment; self-image